Secretin/secretin receptor signaling mediates biliary damage and liver fibrosis in early‐stage primary biliary cholangitis. Issue 9 (28th June 2019) - Kennedy, Lindsey; Francis, Heather; Invernizzi, Pietro; Venter, Julie; Wu, Nan; Carbone, Marco; Eric Gershwin, M.; Bernuzzi, Francesca; Franchitto, Antonio; Alvaro, Domenico; Marzioni, Marco; Onori, Paolo; et al.
ABSTRACT: Primary biliary cholangitis (PBC) primarily targets cholangiocytes and is characterized by liver fibrosis and biliary proliferation. Activation of the secretin (Sct)/secretin receptor (SR) axis, expressed only by cholangiocytes, increases biliary proliferation, liver fibrosis, and bicarbonate secretion. We evaluated the effectiveness of SR antagonist treatment for early‐stage PBC. Male and female dominant‐negative TGF‐β receptor II (dnTGF‐βRII) (model of PBC) and wild‐type mice at 12 wk of age were treated with saline or the SR antagonist, Sec 5‐27, for 1 wk. dnTGF‐βRII mice expressed features of early‐stage PBC along with enhanced Sct/SR axis activation and Sct secretion. dnTGF‐βRII mice had increased biliary proliferation or senescence, inflammation, and liver fibrosis. In dnTGF‐βRII mice, there was increased microRNA‐125b/TGF‐β1/TGF‐β receptor 1/VEGF‐A signaling. Human early‐stage PBC patients had an increase in hepatobiliary Sct and SR expression and serum Sct levels. Increased biliary Sct/SR signaling promotes biliary and hepatic damage during early‐stage PBC.—Kennedy, L., Francis, H., Invernizzi, P., Venter, J., Wu, N., Carbone, M., Gershwin, M. E., Bernuzzi, F., Franchitto, A., Alvaro, D., Marzioni, M., Onori, P., Gaudio, E., Sybenga, A., Fabris, L., Meng, F., Glaser, S., Alpini, G. Secretin/secretin receptor signaling mediates biliary damage and liver fibrosis in early‐stage primary biliary cholangitis. FASEB J. 33, 10269–10279 (2019). www.fasebj.org